DIAGNOSING SARCOPENIA: FUNCTIONAL PERSPECTIVES AND A NEW ALGORITHM FROM ISarcoPRM. - KARA, Murat; KAYMAK, Bayram; FRONTERA, Walter R.; ATA, Ayşe Merve; RICCI, Vincenzo; EKIZ, Timur; Ke-Vin CHANG; Der-Sheng HAN; MICHAIL, Xanthi; QUITTAN, Michael; Jae-Young LIM; BEAN, Jonathan F.; et al. (Journal of Rehabilitation Medicine (Medical Journals Sweden AB), 2021)
Sarcopenia is an important public health problem, characterized by age-related loss of muscle mass and muscle function. It is a precursor of physical frailty, mobility limitation, and premature death. Muscle loss is mainly due to the loss of type II muscle fibres, and progressive loss of motor neurones is thought to be the primary underlying factor. Anterior thigh muscles undergo atrophy earlier, and the loss of anterior thigh muscle function may therefore be an antecedent finding. The aim of this review is to provide an in-depth (and holistic) neuromusculoskeletal approach to sarcopenia. In addition, under the umbrella of the International Society of Physical and Rehabilitation Medicine (ISPRM), a novel diagnostic algorithm is proposed, developed with the consensus of experts in the special interest group on sarcopenia (ISarcoPRM). The advantages of this algorithm over the others are: special caution concerning disorders related to the renin-angiotensin system at the case finding stage; emphasis on anterior thigh muscle mass and function loss; incorporation of ultrasound for the first time to measure the anterior thigh muscle; and addition of a chair stand test as a power/performance test to assess anterior thigh muscle function. Refining and testing the algorithm remains a priority for future research.